2012
DOI: 10.1085/jgp.201210772
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione/thioredoxin systems modulate mitochondrial H2O2 emission: An experimental-computational study

Abstract: The net emission of hydrogen peroxide (H2O2) from mitochondria results from the balance between reactive oxygen species (ROS) continuously generated in the respiratory chain and ROS scavenging. The relative contribution of the two major antioxidant systems in the mitochondrial matrix, glutathione (GSH) and thioredoxin (Trx), has not been assessed. In this paper, we examine this key question via combined experimental and theoretical approaches, using isolated heart mitochondria from mouse, rat, and guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
187
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 70 publications
(123 reference statements)
5
187
0
1
Order By: Relevance
“…On the other hand, GSH is present in millimolar amounts within the cell (24) and represents the largest-capacity redox reserve (25). With respect to cardiac mitochondrial H 2 O 2 scavenging, the relative contributions of GSH-versus thioredoxin-driven H 2 O 2 removal were recently assessed by Aon et al (26), using inhibitors of each pathway. It was found that GSH depletion resulted in a larger increase in mitochondrial H 2 O 2 emission (ϳ19-fold) compared with thioredoxin reductase inhibition (7-fold), although species-dependent differences were observed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GSH is present in millimolar amounts within the cell (24) and represents the largest-capacity redox reserve (25). With respect to cardiac mitochondrial H 2 O 2 scavenging, the relative contributions of GSH-versus thioredoxin-driven H 2 O 2 removal were recently assessed by Aon et al (26), using inhibitors of each pathway. It was found that GSH depletion resulted in a larger increase in mitochondrial H 2 O 2 emission (ϳ19-fold) compared with thioredoxin reductase inhibition (7-fold), although species-dependent differences were observed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Oxygen Consumption Rate Assay-Respiration was assayed with a high throughput automated 96-well extracellular flux analyzer (XF96; Seahorse Bioscience), as described previously (20). Briefly, freshly isolated mitochondria were resuspended in the assay buffer (buffer B) containing 137 mM KCl, 2 mM KH 2 PO 4 , 0.5 mM EGTA, 2.5 mM MgCl 2 , and 20 mM HEPES at pH 7.2, with the presence of 0.2% fatty acid-free BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation and handling of mitochondria were as per prior studies (3). Respiration was assayed with the Seahorse flux analyzer XF96 at 37 Ϯ 1°C as described (5). Mitochondrial protein and H 2O2 were determined as described (5).…”
Section: Methodsmentioning
confidence: 99%